Molecular identification, probiotic characterization, anticancer assessment and encapsulation of lactic acid bacteria isolated from vaginas of Iranian fertile women - Nami, Yousef (2015)
Probiotics are non-pathogenic microorganisms that positively influence their hosts when ingested in adequate amounts. Research on probiotics has increased over the past years. This trend has resulted in the commercialization of probiotic supplements and functional food. Numerous investigations have evaluated the potential of probiotic bacteria for cancer prevention or treatment. Most previous works isolated probiotic bacteria from dairy products or other fermented foods. This study isolated and characterized lactic acid bacteria (LAB) from a healthy vaginal ecosystem. LAB that exhibited probiotic properties were screened for their antimicrobial activity, antibiotic resistance, and anticancer activity. Isolation was performed using preliminary phenotypic screening based on Gram-staining and catalase reaction, followed by 16S rRNA gene sequencing, amplified ribosomal DNA restriction analysis (ARDRA), and repetitive sequence–based PCR fingerprinting. The bacteria isolated from 40 samples were classified into three genera with 13 species, three subspecies, and 45 strains. The combined use of molecular techniques was proven effective for the identification and classification of vaginal LAB, particularly Lactobacillus, Lactococcus, and Enterococcus. The 45 vaginal LAB strains were characterized for their probiotic and therapeutic potentials. Probiotic characterization included in vitro assays of acid and bile salt tolerance, antimicrobial activity, and antibiotic resistance. Results showed that the survival rate of the isolates ranged from 18 to 88% and from 31 to 93% under acidic (pH 3.0) and 0.3% bile salt conditions in a simulated gastrointestinal environment, respectively. The strains from each of the 13 species that demonstrated the highest acid and bile salt tolerance were further evaluated for their antibiotic susceptibility and antimicrobial activity. Results showed that the survival rates of these 13 isolates under acidic and bile salt conditions were higher than 58 and 78%, respectively, qualifying them to be probiotic candidates. All 13 isolates exhibited antimicrobial activity against different pathogenic bacteria. Among the LAB, Lactococcus lactis 2BL showed the strongest antimicrobial activity against 15 pathogenic bacteria. The 13 isolates showed different levels of antibiotic resistance depending on antibiotic used. Among the LAB, Enterococcus avium 7BL and Enterococcus durans 6HL were resistant and sensitive to all nine antibiotics used, respectively. The anticancer effects of the 13 isolates on some human cancer cell lines, such as HeLa, AGS, HT-29, and MCF-7, were also assessed. The human normal cell line HUVEC was used as a control. The cytotoxicity of these strains and the occurrence of apoptotic cells were evaluated using DNA fragmentation, fluorescent microscopy, and flow cytometry. The metabolites produced by Lactobacillus plantarum 5BL, Lactobacillus acidophilus 36YL, Enterococcus faecalis 16H, and Enterococcus lactis 2BL exhibited remarkable anticancer activity against the tested human carcinoma cell lines with no significant cytotoxicity on the HUVEC normal cells. Apoptotic cells were also observed in the cancer cell lines. Finally, the isolates were subjected to encapsulation to improve their bioavailability and survival rate under harsh gastrointestinal conditions. Herbal-based biopolymer matrices, such as alginate, gum arabic, and psyllium, were prepared through extrusion. Three gel formulations, namely, 1, 1.5 and 2% (w/v) alginate, 2% (w/v) alginate + 0.1 and 0.3% (w/v) gum arabic + psyllium, 1.5% (w/v) alginate + 0.3 and 0.5% (w/v) gum arabic + psyllium, and 1% (w/v) alginate + 0.4 and 0.6% (w/v) gum arabic/psyllium were prepared to improve the encapsulation efficiency, gastrointestinal survival, and colonic release rates of the isolates. All encapsulated bacteria exhibited significantly improved (P <0.05) encapsulation efficiency (>98%) and survival rate (>75%) compared with the un-encapsulated bacteria (>45%) under harsh gastrointestinal conditions. The incorporation of gum arabic and psyllium into the alginate gel enhanced encapsulation properties. The use of combination gels for encapsulation improved the survival rate and storage stability of the probiotic strains under gastrointestinal conditions. In conclusion, probiotic bacteria were successfully isolated and characterized from a healthy vaginal ecosystem. These probiotics exhibited antimicrobial activity, antibiotic resistance, and anticancer activity, making these bacteria potential candidates for the development of nutraceutical products.